The effect of 12-weeks foot exercise on blood glucose levels, ankle brachial index, and sensation of protection in diabetes mellitus patients: A quasi-experiment study - Rosliana Dewi; Johan Budhiana; Marina Pra Agustina; Fera Melinda; Astri Zeini Wahida (JKP (Jurnal Keperawatan Padjajaran), 2024)
Background: Diabetes Mellitus (DM) is a global health issue causing nerve damage, blood vessel damage, and leg impairment. Foot exercises can improve risk factors for diabetic foot ulcers, neuropathy symptoms, pressure distribution, joint mobility, and strength in individuals with diabetes.